Pengaruh Model Problem Based Learning terhadap Kemampuan Computational Thinking Berbantuan Media Geogebra - Saniy Basiyroh Manullang; Erlinawaty Simanjuntak (Journal on Education, 2023)
The research aims to determine: (1) the effect of the problem-based learning models on computational thinking skills assisted by geogebra media; (2) student responses to the use of geogebra-assisted problem-based learning models for flat sided geometric material. The type of research is a quasi-experimental with a posttest-only control design, the research population was all students of class VIII SMP Negeri 23 Medan for the 2022/2023 academic year. The sample of this research were 25 students in the experimental class and 25 students in the control class who were taken by cluster random sampling. Data collection on computational thinking skills used a test instrument in the form of a description consisting of 2 questions and student responses using a response questionnaire. The indicators of computational thinking skills that were measured in this research were decomposition, pattern recognition, generalization and abstraction, and algorithmic thinking. Data analysis used the t test (Independent Sample t-Test) for computational thinking skills and percentages for student response questionnaire. Based on the research results obtained (1) there is a significant influence of the problem-based learning model on the ability computational thinking skills assisted by geogebra; (2) there is a positive response from students towards the use of a problem-based learning model assisted by geogebra media on flat sided geometric material.